Images of War: The Place of the War Past of the Parents in the Second Generation’s Identity - Yordanova, Kalina (Journal of Regional Security, 2018)
Memory is an organizing phenomenon for both individuals and societies. Memory allows us to organize our past, foster an identity and ensure our belonging to a group1. Memory plays a central role in the shaping of contemporary identities because it helps us re-construct our identity in relation to our past and other people’s past. How does the memory of war shape the second generation’s identity? By using data collected in 26 families of war survivors from Bosnia and Herzegovina, this paper examines how the identity of the second generation is being shaped by their parents’ war experience.